Results of the interrelation of some financial powers of the state bodies of the general and special financial competence - М. О. Перепелиця (Проблеми Законності, 2015)
Problem Setting. In the article some financial powers of the Verkhovna Rada of Ukraine, of the State Fiscal Service of Ukraine and the National Bank of Ukraine in their interrelation with each other have been analyzed.